Effects of Political Predispositions, Media Use, and Media Evaluation on Policy Malaise among Indonesian and German People - Garnesia, Irma (UI Scholars Hub, 2025)
This study explores a comparative analysis of Germany and Indonesia in the context of the Covid-19 pandemic, emphasizing the importance of addressing cross-cultural dimensions in global health crises—a field that remains underexplored. By enhancing preparedness for future emergencies, the research critically examines whether theoretical assumptions developed in Global North contexts can be meaningfully extended to Global South settings. Specifically, this study hypothesizes that political predispositions, media use, and media evaluation are associated with policy malaise, and investigates these associations in light of cross-cultural differences. Using data from Germany (n = 1,458) and Indonesia (n = 1,043), the findings reveal significant differences between the two nations in the prevalence of political predispositions, media consumption habits, media evaluations, and levels of policy malaise. Further analysis demonstrates that while assumptions developed and tested within Global North contexts are partially applicable to Global South settings, the observed effect sizes vary. Finally, the study situates its results within the distinct cultural and political contexts of each nation, offering a nuanced critique of how social constructs shape policy perceptions in non-Western societies.